Empowerment and Sustainability: Investigating Barriers to Women’s Transition from Higher Education to Empowerment in Brazil - Muhammad Qasim Rana; Angela Lee; José Fernando Rodrigues Bezerra; Guilherme Hissa Villas Boas (Societies)
Gender equality continues to be a global issue, with significant disparities in attention and action between developed and developing nations. Women, in particular, face unique challenges when transitioning from higher education (HE) to empowerment compared to their male counterparts. In many developing countries, barriers to accessing formal education are prevalent, while, in others, despite access to education, women struggle to leverage their learning for societal advancement. This paper adopts the development theory approach by exploring the role of gender equality in fostering sustainable development, emphasizing how women’s empowerment is integral to overall societal progress. This study focuses on Brazil, where, despite high levels of female educational attainment, women still encounter substantial obstacles in transforming their education into meaningful societal empowerment. These challenges include restricted freedom and mobility, deeply ingrained gender norms, violence and harassment, cultural and societal expectations, economic limitations, and family obligations. Survey data were collated from 192 students, alumni, and staff at three academic higher education (HE) institutions in Brazil, utilizing a range of descriptive and inferential statistical analyses to uncover the most significant barriers. This study concludes with policy recommendations aimed at various stakeholders, including government bodies, employers, and other organizations, to support a smoother transition for women from higher education to empowerment. These recommendations include improving workplace policies, enhancing legal protections, and promoting gender equality in leadership roles, all of which are essential to narrowing the gender gap in Brazil.